Burden of Skin Cancer in Older Adults From 1990 to 2021 and Modelled Projection to 2050 - Wang, Ruiyao; Chen, Yangmei; Shao, Xinyi; Chen, Tingqiao; Zhong, Judan; Ou, Yi; Chen, Jin (JAMA dermatology (Chicago, Ill.), 2025)
Skin cancer is a significant public health threat in the aging population, yet data on its burden and trends are limited. To evaluate the global burden of skin cancer among adults 65 years or older from 1990 to 2021, and to project its change to 2050. In this observational study, population-based registry data were extracted from the Global Burden of Diseases (GBD) Study 2021. The database covers 204 countries and territories, ensuring global applicability of the results. Data analysis was conducted from June 9, 2024, to February 18, 2025. Age-standardized rates of prevalence, incidence, deaths, and disability-adjusted life-years (DALYs) were calculated per 100 000 population. Estimated rates of disease burden were calculated for 2050. A worldwide total of 153 993 melanoma, 1 463 424 squamous cell carcinoma (SCC), and 2 802 354 basal cell carcinoma (BCC) instances were estimated for 2021. SCC exhibited the highest age-standardized rate of prevalence (236.91 per 100 000 population; 95% uncertainty interval [UI], 188.23-303.82), deaths (6.16 per 100 000 population; 95% UI, 5.13-6.87), and DALYs (95.50 per 100 000 population; 95% UI, 81.65-106.39), whereas BCC displayed the highest incidence rate (371.97 per 100 000 population; 95% UI, 310.75-439.58). The disease burden was notably greater in male individuals than in female individuals. During the observation period, the global burden of skin cancer among older people demonstrated a general upward trend. Decomposition analysis indicated that population growth was the primary contributor to this increase. Health-inequality analysis revealed a disproportionately higher burden shouldered by countries with higher sociodemographic index (SDI) levels. Frontier analysis identified the countries with considerable potential to mitigate skin cancer. It was anticipated that only incidence and prevalence rates attributable to keratinocyte cancer (KC), along with DALYs rate related to BCC, would increase by 2050. The older population (particularly male individuals and those living in high-SDI countries) is facing a substantial growing burden of skin cancer. Despite the relative incompleteness of KC data and lack of race and ethnicity data, these results highlight the urgency for more effective prevention and management strategies targeting high-risk groups.